Determinants of Audit Fees among Insurance Firms in Nigeria - Goodnews Kolawole Gureje; Okwy Peter Okpala; Collins Sankay Oboh (Copernican Journal of Finance & Accounting, 2025)
This study examined the determinants of audit fees of listed insurance companies in Nigeria, representing developing African countries with emerging capital markets. Panel data set was constructed from the annual reports of ten listed insurance firms from 2017 to 2021, which was analyzed using the Swamy Arora panel regression technique. The results suggest that audit firm size is a significant determinant of audit fees, as client firm size, complexity, and profitability did not significantly impact audit fees. As part of its contribution to the literature, the study establishes that audit firm size is directly associated with audit fees, as larger audit firms charge more as audit fees than smaller audit firms. This evidence can be used in a standard-setting process to promote high audit quality and limit corporate collapses. In addition, the study adds to the limited literature on audit fee determinants in the insurance industry, which has long been neglected as most studies are focused on manufacturing companies. The evidence will guide management in the insurance industry in negotiating a fair audit fee.